Very busy spider (The) - Carle, Eric (New York : Philomel Books, 1984)
The farm animals try to divert a busy little spider from spinning her web, but she persists and produces a things of both beauty and usefulness. The picture may be felt as well as seen.
Keywords: Toy and movable books-Specimens; Spiders-Fiction; Spider webs-Fiction; Domestic animals-Fiction; Toy and movable books